The effects of exercise on muscle strength, body composition, physical functioning and the inflammatory profile of older adults: a systematic review. Issue 1 (January 2017) - Liberman, Keliane; Forti, Louis N.; Beyer, Ingo; Bautmans, Ivan
Abstract : Purpose of review: This systematic review reports the most recent literature regarding the effects of physical exercise on muscle strength, body composition, physical functioning and inflammation in older adults. All articles were assessed for methodological quality and where possible effect size was calculated. Recent findings: Thirty-four articles were included – four involving frail, 24 healthy and five older adults with a specific disease. One reported on both frail and nonfrail patients. Several types of exercise were used: resistance training, aerobic training, combined resistance training and aerobic training and others. In frail older persons, moderate-to-large beneficial exercise effects were noted on inflammation, muscle strength and physical functioning. In healthy older persons, effects of resistance training (most frequently investigated) on inflammation or muscle strength can be influenced by the exercise modalities (intensity and rest interval between sets). Muscle strength seemed the most frequently used outcome measure, with moderate-to-large effects obtained regardless the exercise intervention studied. Similar effects were found in patients with specific diseases. Summary: Exercise has moderate-to-large effects on muscle strength, body composition, physical functioning and inflammation in older adults. Future studies should focus on the influence of specific exercise modalities and target the frail population more.